Les prémices d’une nouvelle stratégie américaine en Asie - Morgane Farghen (MONDE CHINOIS NOUVELLE ASIE, 2016)
Toward a new America Strategy in Asia: beyond conflicts, converging toward a consistent approach The re-initiation of American politics regarding Asia is being built on a geopolitical schema that is China-centered, and one that is in opposition of the former approach, that was judged to be too favorable and lenient, as well as responsible for a decline in the security situation. The influence upon strategic adversaries, and the restoration of the authority among the relations with those adversaries, has emerged as a dominant force in domestic political conflicts. Keywords: Asia Pacific, China, United States, Nuclear policy, Security, Defense, Foreign policy